Development of thermally sprayed niobium carbide-based hardmetal coatings - Gehlen, Larissa Rossi (2024)
Thermally sprayed WC-CoCr and Cr3C2-NiCr hardmetal coatings are widely used in industrial components subject to severe working conditions as a method of protection against wear and corrosion. However, the aforementioned compositions have restrictions that limit their applications: WC-CoCr has thermal expansion incompatibility with steel substrates and oxidises catastrophically at T > 400-500 °C, while Cr3C2-NiCr offers lower wear protection at low and moderate temperatures. Despite the scarce literature on thermally sprayed NbC-based coatings, promising wear resistance results have been obtained with NbC-based bulk hardmetal formulations over a wide temperature range. In this context, in the present work, different compositions of NbC-based hardmetal coatings were sprayed by the High-Velocity Oxygen Fuel (HVOF) process on stainless steel substrates aiming to achieve an adequate balance of different tribological and electrochemical performances. The production of NbC-based coatings has been developed in two steps: in the first step, NbC particles were homogeneously dispersed in either 25 vol.% or 40 vol.% of a Ni-20wt.%Cr matrix. In the second step, NbC particles were dispersed in 40vol.% of a matrix containing Fe-20 wt.%Cr-15 wt.%Mo. In both steps, the homogenization of the NbC particles in the binder phase was carried out by mechanical alloying through the process by High-Energy Ball Milling (HEBM). Different sets of thermal spray parameters were employed and the microstructure, Vickers microhardness, abrasion resistance, dry sliding wear resistance (from room temperature up to 600 °C) and corrosion resistance of the coatings were studied. The results were compared to those obtained on reference coatings (WC-CoCr, Cr3C2- NiCr) and other alternative hardmetal coatings (TiC-40NiCr and TiC-25NiCr). Regardless of the process parameters, NbC-based coatings showed low porosity (< 2%) and microhardness values of around 900 HV300 (NbC-25NiCr) and 1000 HV300 (NbC-40NiCr and NbC-FeCrMo). The NbC-NiCr coatings presented dry sliding wear resistance intermediate between those of conventional WC-CoCr and Cr3C2-NiCr coatings, and comparable to that of TiC-NiCr, despite producing higher friction coefficients. NbC-FeCrMo coatings showed low resistance to sliding wear at low and moderate temperatures (f 300 °C), but high resistance at high temperatures, particularly at 400 °C. All the NbCbased coatings exhibited limited three-body abrasion resistance due to the occurrence of some brittle fractures along with grooving due to abrasion. The NbC-NiCr coatings, especially the one with 40vol.% matrix phase exhibited excellent corrosion resistance: the corrosion current densities (~0.1 μA/cm2) and passive current densities (<1 μA/cm2) were lower than the corresponding values found for all reference coatings. Thus, NbC-NiCr coatings are promising for applications where a good balance between corrosion resistance and wear resistance over a wide temperature range is required, while the NbC-FeCrMo coating is particularly promising for sliding wear applications in the range of 400°C to 600°C.